2004
DOI: 10.1186/1471-2431-4-1
|View full text |Cite
|
Sign up to set email alerts
|

Caregiving process and caregiver burden: Conceptual models to guide research and practice

Abstract: BackgroundParental care for a child with a developmental disability is an enormous responsibility, one that can far exceed that of typical parental care. While most parents adapt well to the situation of caring for a child with a disability, some do not. To understand parents' adaptations to their children's disabilities, the complex nature of stress processes must be accounted for and the constructs and factors that play a role in the caregiving must be considered.DiscussionEvidence suggests that there is con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

20
367
3
14

Year Published

2007
2007
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 389 publications
(414 citation statements)
references
References 58 publications
20
367
3
14
Order By: Relevance
“…Contrary to an emerging body of literature in pediatrics that describes a positive correlation between the health of children with chronic illnesses and their caregivers' quality of life, 12,42 we did not find large immediate improvements in caregiver quality of life and decrease in stress as their chil- dren's quality of life improved. This may be related to the number of parents in our sample being too small to detect such changes or that changes in longer-term (greater than 6 months or 1 year) quality of life not being reflected by short-term assessment.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Contrary to an emerging body of literature in pediatrics that describes a positive correlation between the health of children with chronic illnesses and their caregivers' quality of life, 12,42 we did not find large immediate improvements in caregiver quality of life and decrease in stress as their chil- dren's quality of life improved. This may be related to the number of parents in our sample being too small to detect such changes or that changes in longer-term (greater than 6 months or 1 year) quality of life not being reflected by short-term assessment.…”
Section: Discussioncontrasting
confidence: 99%
“…12,13 Previous studies of fundoplication in children with NI, GERD, and dysfunctional swallowing reported surgical mortality rates between 1% and 3% and other complications between 4% and 39%, reflecting the medical fragility of these children. 5,14 -18 Some of these studies had longitudinal follow-up and reported long-term data.…”
mentioning
confidence: 99%
“…Damage to the quality of life in the group of mothers of ASD children has been shown in various studies (1,3,6,7,15,21,22). The quality of life in damaged families with severe disabilities can be adjusted through various factors such as the social support, socioeconomic condition, and the adaptive strategies (23).…”
Section: Discussionmentioning
confidence: 99%
“…O nascimento de uma criança com PC pode originar alterações familiares com diferentes graus de intensidade 4 . A saúde psicológica e física dos cuidadores pode ser fortemente influenciada pelo comportamento da criança e pela demanda de cuidado 5 . O cuidador primário da criança com PC, que normalmente é a mãe, altera sua própria vida em função de melhorar a condição de sua criança 1 .…”
unclassified